Local conservation action requires ethical investments in global digital equity - Tabor. K. M.; Stavros, N.; Holland, M. B. (2024)
Satellite remote sensing is vital for monitoring anthropogenic changes and for alerting us to escalating environmental threats. With recent technological advances, a variety of satellite-based monitoring systems are available to aid conservation practitioners. Yet, documented knowledge of who uses near-real-time satellite-based monitoring and how these technologies are applied to inform conservation decisions is sparse. Through an online survey and semi-structured interviews, we explored how developers and users leverage conservation early-warning and alert systems (CEASs) for enhanced conservation decisions. Some 167 developers and users of near-real-time fire and forest monitoring systems from 40 countries participated in this study. Globally, respondents used 66 unique CEASs. The most common applications were for education and awareness, fire/disaster management and law enforcement. Respondents primarily used CEASs to enforce land-use policies and deter illegal activities, and they perceived these tools as underutilized for incentivizing policy compliance or conservation. Respondents experienced inequities regarding system access, exposure and ability to act upon alert information. More investments in capacity-building, resources and action plans are needed to better link information to action. Implementing recommendations from this research can help us to increase the accessibility and inclusivity of CEAS applications to unlock their powerful capabilities for achieving conservation goals.